Botulinum Toxin Is Effective in the Management of Neurogenic Dysphagia. Clinical-Electrophysiological Findings and Tips on Safety in Different Neurological Disorders - Alfonsi, Enrico; Restivo, Domenico A.; Cosentino, Giuseppe; De Icco, Roberto; Bertino, Giulia; Schindler, Antonio; Todisco, Massimiliano; Fresia, Mauro; Cortese, Andrea; Prunetti, Paolo; Ramusino, Matteo C.; Moglia, Arrigo; et al. (Frontiers in Pharmacology, 2017)
Background and Aims: Neurogenic dysphagia linked to failed relaxation of the upper esophageal sphincter (UES) can be treated by injecting botulinum toxin (BTX) into the cricopharyngeal (CP) muscle. We compared the effects of this treatment in different neurological disorders with dysphagia, to evaluate its efficacy over time including the response to a second injection. Materials and Methods: Sixty-seven patients with neurogenic dysphagia associated with incomplete or absent opening of the UES (24 with brainstem or hemispheric stroke, 21 with parkinsonian syndromes, 12 with multiple sclerosis, and 10 with spastic-dystonic syndromes secondary to post-traumatic encephalopathy) were treated with the injection of IncobotulinumtoxinA (dose 15-20 U) into the CP muscle under electromyographic guidance. The patients were assessed at baseline and after the first and second treatment through clinical evaluation and fiberoptic endoscopy of swallowing, while their dysphagia was quantified using the Dysphagia Outcome and Severity Scale (DOSS). An electrokinesiographic/electromyographic study of swallowing (EES) was performed at baseline. Results: Most patients responded to the first BTX treatment: 35 patients (52.2%) were classified as high responders (DOSS score increase > 2 levels), while other 19 patients (28.4%) were low responders (DOSS score increase of ≤ 2 levels). The effect of the first treatment usually lasted longer than 4 months (67%), and in some cases up to a year. The treatment efficacy remained high also after the second injection: 31 patients (46.3%) qualified as high responders and other 22 patients (32.8%) showed a low response. Only in the parkinsonian syndromes group we observed a reduction in the percentage of high responders as compared with the first treatment. Side effects were mostly mild and reported in non-responders following the first injection. A severe side effect, consisting of ingestion pneumonia, was observed following the second BTX injection in two patients who had both been non-responders to the first. Non-responders were characterized electromyographically by higher values of the oropharyngeal interval. Conclusions: These findings confirm the effectiveness of IncobotulinumtoxinA injection in the treatment of neurogenic dysphagia due to hyperactivity and relaxation failure of the UES. Caution should be used as regards the re-injection in non-responders to the first treatment.